Epidemiology of adolescent substance use in London schools. Issue 6 (26th September 2015) - Penney, J.; Dargan, P.I.; Padmore, J.; Wood, D.M.; Norman, I.J.
Abstract : Background: Alcohol and substance use in adolescence can be associated with a range of health, emotional, social, behavioural and legal problems. There has been a change in the recreational drugs available to users in recent years; however, little is known about how this impacts the youngest and most vulnerable population of substance users. Aim: To investigate the prevalence of substance use among children aged 15–18 years in London schools. Design: Questionnaire survey. Method: Students aged 15–18 years in three London schools self-completed the questionnaire which collected demographic data (age, gender and ethnicity) and data on frequency of use of alcohol, tobacco and classical recreational drugs and novel psychoactive substances. Results: Completed surveys were available from 533 students (47.8% of those invited to participate). One hundred thirteen (20.4%) students reported lifetime use of at least one recreational drug, cannabis (96, 18.7%) was commonly reported and only 6 (1.1%) reported use of a novel psychoactive substance. A total of 250 (47.8%) reported using alcohol at least once; those from White and Mixed ethnic groups were more likely to report using alcohol than those in other ethnic groups. A total of 382 (74.2%) students reported using tobacco at least once, and students from ethnic minorities were more likely to smoke than their White counterparts. Conclusion: This study supports previous findings that alcohol and drug use are declining in adolescents in UK. There are different patterns of substance use amongst different ethnic groups; this is important to schools and policymakers planning interventions related to substance use in school-aged children.